The Importance Of Work Life Balance To Improve Work Satisfaction - Nasution Nasution; Muhammad Ali (Universitas Negeri Gorontalo, 2020)
Work-Life Balance as an independent variable consists of three indicators of balance, namely the balance of time, the balance of involvement and the balance of satisfaction. The job satisfaction as a dependent variable is divided into four factors, namely psychological factors, social factors, physical factors and financial factors. This study aims to determine the effect of Work-life balance on employee Job Satisfaction at the Bima Regency Social Service. This type of research uses causal quantitative methods with primary data sources obtained from interviews and questionnaires distributed to 60 respondents. The sampling technique used is simple random interconnection with the Slovin formula. The analytical tool used is the validity and reliability test, simple linear regression, correlation coefficient, coefficient of determination and T-test. The results of this study indicate that Work-life balance has a significant effect on job satisfaction of Bima Regency Social Service employees. This can be seen from the significant value of 0.000